Properties and dynamics of mesoscale eddies in Fram Strait from a comparison between two high-resolution ocean-sea ice models - Wekerle, Claudia; Hattermann, Tore; Wang, Qiang; Crews, Laura; von Appen, Wilken-Jon; Danilov, Sergey (Ocean Science, 2020)
Fram Strait, the deepest gateway to the Arctic Ocean, is strongly influenced by eddy dynamics. Here we analyse the output from two eddy-resolving models (ROMS – Regional Ocean Modeling System; FESOM – Finite-Element Sea-ice Ocean Model) with around 1 km mesh resolution in Fram Strait, with a focus on their representation of eddy properties and dynamics. A comparison with mooring observations shows that both models reasonably simulate hydrography and eddy kinetic energy. Despite differences in model formulation, they show relatively similar eddy properties. The eddies have a mean radius of 4.9 and 5.6 km in ROMS and FESOM, respectively, with slightly more cyclones (ROMS: 54 %, FESOM: 55 %) than anticyclones. The mean lifetime of detected eddies is relatively short in both simulations (ROMS: 10 d, FESOM: 11 d), and the mean travel distance is 35 km in both models. More anticyclones are trapped in deep depressions or move toward deep locations. The two models show comparable spatial patterns of baroclinic and barotropic instability. ROMS has relatively stronger eddy intensity and baroclinic instability, possibly due to its smaller grid size, while FESOM has stronger eddy kinetic energy in the West Spitsbergen Current. Overall, the relatively good agreement between the two models strengthens our confidence in their ability to realistically represent the Fram Strait ocean dynamics and also highlights the need for very high mesh resolution.